Robust and informative microsatellite markers for genetic improvement of Indian sesame (Sesamum indicum L.): Robust and informative microsatellite markers for genetic improvement of Indian sesame (Sesamum indicum L.) - H H KUMARASWAMY; K T RAMYA; J JAWAHARLAL; P RATNAKUMAR (Journal of Oilseeds Research, 2020)
Quality of sesame seed oil is superior but seed yields have stagnated at abysmally low levels. Marker-assisted genetic improvement holds key to break the yield-barrier. Robust molecular markers are the indispensable prerequisites of marker-assisted breeding. Microsatellites are the easy-to-use and codominant molecular markers widely used across crop species. In the present study, a set of 180 robust and informative SSR markers have been identified from about 400 SSR based primers tested and thus adding more markers for utilization in different marker assisted breeding programmes of sesame.